Deep phenotyping of frontal lobe epilepsy compared to other epilepsy syndromes. Issue 6 (27th May 2022) - Wee, Ryan; Nash, Adina; Angus-Leppan, Heather
Abstract : Background: Epilepsy syndromes differ in their demography, clinical manifestations and investigation findings. Frontal lobe epilepsy (FLE), a focal epilepsy syndrome with a heterogeneous presentation, is understudied and often misdiagnosed. We sought to phenotype the diagnostic features of FLE and to differentiate FLE from other epilepsy syndromes. Methods: 1481 prospective cases of epilepsy, diagnosed based on International League against Epilepsy criteria, were identified from a neurology centre in London. Results: 166 patients had FLE based on clinical findings and investigations. 97 had electroencephalogra- phy (EEG) foci in frontal areas (definite FLE) while 69 patients with FLE had no frontal EEG foci (probable FLE). Definite and probable FLE did not differ in any other features. Systematic comparisons of FLE and other epilepsy syndromes revealed demographic, clinical and investigation features that differentiated FLE from the other syndromes; these features included an underlying structural or metabolic aetiology, abnormalities on MRI and the absence of intellectual disability. Conclusions: FLE is a varied clinical syndrome characterised by dyscognitive symptoms and a predomi- nantly structural or metabolic aetiology usually identified with MRI. There was no difference in the clinical features of definite and probable FLE. This large case series provides further insights into the hallmark features of FLE. ryan.wee.13@ucl.ac.uk